River flood hydrology proceedings of the symposium organized by, and held at, the Institution of Civil Engineers on Thursday, 18 March, 1965. (Institution of Civil Engineers, 1966)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a symposium held on 18 March 1965.